Consumers' Perspective On 5V And 4P Hand Phone Models In Iran - Fereidooni, Shirzad (2009)
The main objective of this research is the evaluation of the relationship between the two models of 5V and 4P and its effects on the decision making process of customers of the mobile phone market of Tehran.